DISCRIMINANT MODELS OF SEBORRHEIC DERMATITIS POSSIBILITIES OF OCCURRENCE AND COURSE IN MEN AND WOMEN DEPENDING ON THE CHARACTERISTICS OF ANTHRO-SOMATOTYPOLOGICAL PARAMETERS - Khasawneh, A.R.; Dmytrenko, S.V.; Shevchuk, Yu.G.; Kondratiuk, A.I.; Kryvonis, T.G. (World of Medicine and Biology, 2022)
Based on anthropometric indicators developed reliable discriminant models that allow to predict with high probability the possibility of generalized fatty seborrheic dermatitis in Ukrainian men and women (respectively correctness of 87.7 % and 91.8 % of cases, Wilks' Lambda statistics=0.063 and 0.174). The constructed models in men most often include girth (42.8 %) and thickness of skin and fat folds (28.6 %); in women – the thickness of skin and fat folds (42.8 %) and body diameters (28.6 %). In the constructed models, the greatest contribution to discrimination in men is made by the shoulder girths in the tense and unstressed state, and in women – the thickness of the skin and fat folds on the thighs and the width of the shoulders.
Keywords: skin diseases; seborrheic dermatitis; Ukrainian men and women; body structure and size; anthropometry; discriminant analysis